Visualizing global trade flows of copper: An examination of copper contained in international trade flows in 2014 - Luis Alberto Tercero Espinoza; Marcel Soulier; Stefan Haag (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2016)
This Working Paper presents a brief but comprehensive graphical overview of copper contained in international trade, from copper concentrates through to finished products. Extensive data checks and a simple consolidation method were performed before visualizing the data on world maps. While data were collected and anlyzed for the period 1992-2014, the year 2014 is used here to follow the global journey of copper from mine to final users.
urn:nbn:de:0011-n-3937549
Keywords: 330; copper; trade balances; embedded copper; foreign trade